2003
DOI: 10.1007/s10350-004-6651-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Predictive Value of a Bowel Symptom Questionnaire in Identifying Perianal and Anal Sphincter Trauma After Vaginal Delivery

Abstract: A bowel-habit questionnaire will detect approximately 60 percent of females who sustain external sphincter tears after vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…Frudinger et al [11] found that a bowel symptom questionnaire could predict only 57% of sphincter defects following childbirth. Anal inspection and digital rectal examination are basic assessment tools of sphincter integrity and function.…”
Section: Introductionmentioning
confidence: 99%
“…Frudinger et al [11] found that a bowel symptom questionnaire could predict only 57% of sphincter defects following childbirth. Anal inspection and digital rectal examination are basic assessment tools of sphincter integrity and function.…”
Section: Introductionmentioning
confidence: 99%
“…Sultan et al 20 observed that 30 percent of anal sphincter lesions were asymptomatic. Frudinger et al 19 observed that among 43.2 percent of females presenting ultrasonographic evidence of anal sphincter tears, only 27.6 percent complained of deterioration of anal continence and that among the 17.5 percent of females with anal symptoms only 17.5 percent presented ultrasonographic evidence of anal sphincter tears. It is generally agreed that anal sensation is not always correlated with low anal squeeze pressure and ultrasonographic evidence of sphincter defects.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study demonstrated that only 60 percent of females with anal sphincter tear consecutive to vaginal delivery were detected using a postpartum bowel-habits questionnaire. 19 Use of a questionnaire for evaluation of anal symptoms is associated with a poor sensitivity but good specificity. Another potential problem is the understandability of the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms subsequent to perineal tears include flatulence incontinence, pathological urge to defecate and, more rarely, fecal incontinence with the consistency ranging from watery to firm stools. The frequency of these symptoms tends to increase over the years following the birth 7 , 8 , 9 .…”
Section: Guidelinementioning
confidence: 99%